2018
DOI: 10.1007/s13538-018-0575-7
|View full text |Cite
|
Sign up to set email alerts
|

The Kantowski-Sachs Quantum Model with Stiff Matter Fluid

Abstract: In this paper we study the quantum cosmological Kantowski-Sachs model and solve the Wheeler-DeWitt equation in minisuperspace to obtain the wave function of the corresponding universe. The perfect fluid is described by the Schutz's canonical formalism, which allows to attribute dynamical degrees of freedom to matter. The time is introduced phenomenologically using the fluid's degrees of freedom. In particular, we adopt a stiff matter fluid. The viability of this model is analyzed and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Using similar variables as in Eqs. (92) with Σ = 0 and replacing the normalization factor D = H 2 + 3 R 6 , where 3 R denotes the 3-Ricci curvature of spatial surfaces calculated in (86) by Eq. ( 91), we obtain the system…”
Section: Flrw Metric With Positive Curvaturementioning
confidence: 99%
“…Using similar variables as in Eqs. (92) with Σ = 0 and replacing the normalization factor D = H 2 + 3 R 6 , where 3 R denotes the 3-Ricci curvature of spatial surfaces calculated in (86) by Eq. ( 91), we obtain the system…”
Section: Flrw Metric With Positive Curvaturementioning
confidence: 99%
“…and modified gravity f (R) [22,23,24,25,26,27]. The Schutz's formalism is used even with success in anisotropic quantum cosmology [28,29,30,31,32,33,34], bouncing cosmologies [35,36,37] or very recently on Brans-Dicke theory and scalar-tensor theories [38,39,40,41].…”
Section: The Schutz's Formalism In Quantum Cosmologymentioning
confidence: 99%
“…Different cosmological scenarios can be studied by varying the fluid considered by choosing different values of γ [19,20,21], models with two perfect fluids, exotic matter and modified gravity f (R) [22,23,24,25,26,27]. The Schutz's formalism is used even with success in anisotropic quantum cosmology [28,29,30,31,32,33,34], bouncing cosmologies [35,36,37] or very recently on Brans-Dicke theory and scalar-tensor theories [38,39,40,41].…”
Section: The Schutz's Formalism In Quantum Cosmologymentioning
confidence: 99%
“…On the other hand, an exact solution of field equations for Kantowski-Sachs background space with cosmological constant was found in [43]. For some other we refer the reader to [21,[44][45][46][47][48][49][50][51][52][53][54][55] and references therein. In the case of Einstein-Aether theory in [56] the authors presented a generic static spherical symmetric solution, where it has been shown that the Schwarzschild spacetime is recovered.…”
Section: Introductionmentioning
confidence: 99%